2020
DOI: 10.3390/v12101144
|View full text |Cite
|
Sign up to set email alerts
|

Tracking SARS-CoV-2 in Sewage: Evidence of Changes in Virus Variant Predominance during COVID-19 Pandemic

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), responsible for the ongoing coronavirus disease (COVID-19) pandemic, is frequently shed in faeces during infection, and viral RNA has recently been detected in sewage in some countries. We have investigated the presence of SARS-CoV-2 RNA in wastewater samples from South-East England between 14th January and 12th May 2020. A novel nested RT-PCR approach targeting five different regions of the viral genome improved the sensitivity of RT-qPCR assays an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
142
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 52 publications
5
142
0
2
Order By: Relevance
“…Had this testing been in place at the time, it would have provided public health officials with more time to coordinate and implement actions to slow the spread of disease. A study in the UK reported that clinical testing underestimated the prevalence of COVID-19 and that large reductions in SARS-CoV-2 RNA in wastewater coincided with lockdowns (Martin et al 2020 ).…”
Section: Benefits Of Wastewater-based Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Had this testing been in place at the time, it would have provided public health officials with more time to coordinate and implement actions to slow the spread of disease. A study in the UK reported that clinical testing underestimated the prevalence of COVID-19 and that large reductions in SARS-CoV-2 RNA in wastewater coincided with lockdowns (Martin et al 2020 ).…”
Section: Benefits Of Wastewater-based Epidemiologymentioning
confidence: 99%
“…A comprehensive study using WGS assessed the geographic and temporal distribution of SARS-CoV-2 lineages across Europe (Alm 2020) and this approach was used in the Netherlands to identify separate introductions to mink farms (Oreshkova et al 2020 ). A study in England used WBE to detect virus variants that were particularly prevalent in the UK and also identified the increasing dominance of the Spike protein G614 variant using Whole Genome sequencing (WGS) (Martin et al 2020 ). Similarly, phylogenetic analyses of a SARS-CoV-2 genome from a WWTP in Bozeman, Montana (USA), showed that it was more closely related to isolates from California and Australia than the Wuhan WA1 linage (Nemudryi et al 2020 ).…”
Section: Benefits Of Wastewater-based Epidemiologymentioning
confidence: 99%
“…human excretion), and catchment population, the catchment-level prevalence can be estimated. To date, the existence of SARS-CoV-2 virus RNA in wastewater have been confirmed in many countries, including, Australia [8] , [9] , Brazil [10] , China [11] , [12] , Czech Republic [13] , Ecuador [14] , France [15] , [16] , India [17] , [18] , Italy [19] , [20] , [21] , [22] , Japan [23] , Spain [24] , [25] , the Netherlands [7] , United Kingdom (UK) [26] , Slovenia [27] , Sweden [28] , United Arab Emirates (UAE) [29] , [30] and United States (USA) [31] , [32] , [33] , [34] , [35] . The successful detection of SARS-CoV-2 virus RNA through reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and sequencing approaches in wastewater demonstrated the high potential of applying WBE as a tool to estimate the COVID-19 prevalence in their communities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lodder and de Roda Husman [22] provided perspective on “SARS-CoV-2 in wastewater: potential health risk, but also data source”, saying that the wastewater could be a sensitive surveillance system and early warning tool in pandemic. Wastewater-based epidemiology (WBE) has been quickly and widely tested in many countries and regions around the world, such as Spain [11] , [23] , Italy [8] , [24] , [25] , UK [26] , Netherlands [13] , USA [27] , [28] , India [14] , [29] , Japan [15] , Germany [7] , Australia [17] , [30] , and United Arab Emirates [16] . Many countries, such as Ireland and China, were conducting such kind of research to closely monitor wastewater related SARS-CoV-2.…”
Section: Overall Publications Related To Weekly Count Case Numbers Ofmentioning
confidence: 99%